WEIRD Commerce at the Ghetto Biennale - Cussans, J (Bookworks, 2016)
In 2010 three psychology professors at the University of British Columbia wrote a paper for the journal of Behavioral and Brain Sciences entitled ‘The Weirdest People in the World?’ WEIRD, an acronym for Western, Educated, Industrialised, Rich and Democratic, was used to describe the kinds of society that people taken as representative of ‘normality’ in the majority of human behavioural studies conducted at (mainly American) universities come from. I’m using it here to designate, in the most general terms, the social background of the visiting artists to the Ghetto Biennale in Haiti. The basic proposition is that WEIRD artists tend to have very specific ideas about art’s meaning, value and social function, received from WEIRD art schools, university educations and participation in WEIRD art worlds, and that these ideas are not necessarily shared by people who have not been so conditioned by that realm. The WEIRD outlook is generally utopian, idealistic, progressive and socially responsible, and often sees art as antagonistic to, or somehow corrupted by pragmatism, or commercial, monetary aims. As Hans Abbing argues in Why Are Artists Poor?, such beliefs are based largely on the thinlyveiled Romantic myth that art is somehow ‘holy’. I would add that such holiness is bolstered by the dominance of Marxist critical theory in WEIRD art schools and universities, which transforms these quasi-theological beliefs about art’s sacred purposes into critical, anti-capitalist and socially emancipatory ones.